Edukasi Pengenalan Fikih Wanita Kepada Remaja di Ponpes At-Taubah Garum Kabupaten Blitar - Ainur Rofiqoh; Ilham Achmad Asfi Burhanudin (LP3M IAIFA Kediri, 2021)
This learning education aims to provide additional knowledge about fiqh, especially menstruation to adolescents at the Islamic boarding school at Taubah, Garum sub-district, Blitar City. Sometimes for some girls who have just entered the age of aqil baligh, it is difficult to accept the changes that occur in them. This is due to a lack of knowledge and lack of attention from parents in paying attention to their children. The purpose of this education is to increase women's knowledge of fiqh, especially those that discuss menstruation. The researcher provides several main topics of discussion, namely, (1) the understanding of menstruation according to language and terms (2) the time of menstruation, starting from the initial age limit for a woman to be declared menstruating at the age of 9 years, (3) the minimum period of menstruation, generally menstruation and the maximum length of menstruation, (4) things that are prohibited while menstruating, (5 ) obligatory bathing after menstruation and (6) procedures for replacing the prayer after being purified from menstruation.